Nitric Oxide Alters the Pattern of Auxin Maxima and PIN-FORMED1 During Shoot Development - Sánchez-Vicente, Inmaculada; Lechón, Tamara; Fernández-Marcos, María; Sanz, Luis; Lorenzo, Oscar (Frontiers in Plant Science, 2021)
Hormone patterns tailor cell fate decisions during plant organ formation. Among them, auxins and cytokinins are critical phytohormones during early development. Nitric oxide (NO) modulates root architecture by the control of auxin spatial patterns. However, NO involvement during the coordination of shoot organogenesis remains unclear. Here, we explore the effect of NO during shoot development by using a phenotypic, cellular and genetic analysis in Arabidopsis thaliana and get new insights into the characterization of NO-mediated leaf-related phenotypes. NO homeostasis mutants are impaired in several shoot architectural parameters, including phyllotactic patterns, inflorescence stem elongation, silique production, leaf number and margin. Auxin distribution is a key feature for tissue differentiation and need to be controlled at different levels (i.e. synthesis, transport and degradation mechanisms). The phenotypes resulting from the introduction of the cue1 mutation in the axr1 auxin resistant and pin1 backgrounds exacerbates the relationship between NO and auxins. Using the auxin reporter DR5:GUS, we observed an increase in auxin maxima under NO-deficient mutant backgrounds and NO scavenging, pointing to NO-ASSOCIATED 1 (NOA1) as the main player related to NO production in this process. Furthermore, polar auxin transport is mainly regulated by PIN-FORMED 1 (PIN1), which controls the flow along leaf margin and venations. Analysis of PIN1 protein levels shows that NO controls its accumulation during leaf development, impacting the auxin mediated mechanism of leaf building. With these findings, we also provide evidence for the NO opposite effects to determine root and shoot architecture, in terms of PIN1 accumulation under NO overproduction.